Effect of Fertilizer Doses on Nutrient Uptake and Use Efficiencies under Different Rice Cultivation Methods - RAFI, SHAIK MOHAMMAD; THAKUR, A.K.; VERMA, OM PRAKASH; BHOL, RAJKUMARI; PANIGRAHI, KAUSHIK KUMAR; SHATPATHY, PRABHASMITA (Journal of the Indian Society of Coastal Agricultural Research, 2025)
A field experiment was conducted at ICAR-Indian Institute of Water Management Research Farm, Mendhasal, Odisha, during the Rabi (winter) season of 2024 to study the effect of different crop management practices in rice with varying NPK doses on grain yield, nutrient uptake, and their use efficiencies. The experiment was laid out in a factorial split-plot design with three replications, comprised of two crop establishment methods of rice, viz. system of rice intensification (SRI) and conventional transplanting system (CTS) in the main plot and the sub-plot treatments were T1-0% of the recommended dose of fertilizer (RDF), T2-25% of RDF, T3- 50% of RDF, T4- 75% of RDF, T5- 100% of RDF and T6- 125% of RDF. The recommended dose of fertilizers was 80 kg N, 40 kg P2O5, and 40 kg K2O ha-1. It was found that the highest grain yield for both SRI (5.89 t ha-1) and CTS (4.56 t ha-1) was observed in T5- 100% RDF.  Overall, SRI produced a 30% higher grain yield than CTS. The uptake of NPK increased significantly in both grains and straws of crops grown under SRI. N, P, and K uptake in grains increased by 33.1%, 39.2%, and 37% more under SRI than CTS. The agronomic efficiency (AE) of SRI was 27% higher than that of the CTS crop. Under SRI, nearly 43 kg of grain was produced with the application of 1 kg of fertilizer. In contrast, with CTS, only 31 kg of grain was produced with the application of 1 kg of fertilizer, a 28% decrease in the partial factor productivity of applied fertilizer compared to SRI.